A tale of two cities: the cost, price-differential and affordability of current and healthy diets in Sydney and Canberra, Australia - Amanda J. Lee; Sarah Kane; Lisa-Maree Herron; Misa Matsuyama; Meron Lewis (BMC, 2020)
Abstract Background The perception that healthy foods are more expensive than unhealthy foods has been reported widely to be a key barrier to healthy eating. However, assessment of the relative cost of healthy and unhealthy foods and diets is fraught methodologically. Standardised approaches to produce reliable data on the cost of total diets and different dietary patterns, rather than selected foods, are lacking globally to inform policy and practice. Methods This paper reports the first application, in randomly selected statistical areas stratified by socio-economic status in two Australian cities, of the Healthy Diets Australian Standardized Affordability and Pricing (ASAP) method protocols: diet pricing tools based on national nutrition survey data and dietary guidelines; store sampling and location; determination of household incomes; food price data collection; and analysis and reporting. The methods were developed by the International Network on Food and Obesity/NCD Research, Monitoring and Action Support (INFORMAS) as a prototype of an optimum approach to assess, compare and monitor the cost and affordability of diets across different geographical and socio-economic settings and times. Results Under current tax policy in Australia, healthy diets would be 15-17% less expensive than current (unhealthy) diets in all locations assessed. Nevertheless, healthy diets are likely to be unaffordable for low income households, costing more than 30% of disposable income in both cities surveyed. Households spent around 58% of their food budget on unhealthy food and drinks. Food costs were on average 4% higher in Canberra than Sydney, and tended to be higher in high socioeconomic locations. Conclusions Health and fiscal policy actions to increase affordability of healthy diets for low income households are required urgently. Also, there is a need to counter perceptions that current, unhealthy diets must be less expensive than healthy diets. The Healthy Diets ASAP methods could be adapted to assess the cost and affordability of healthy and unhealthy diets elsewhere.